PENGARUH PERAN KEPALA SEKOLAH SEBAGAI INOVATOR TERHADAP PENGEMBANGAN PEMBELAJARAN DIGITAL DI MTS AL-IMAROH BERDASARKAN PERSEPSI GURU - Riana Handayani Hasan; Hinggil Permana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of the role of school principals as innovators on the development of digital learning in MTs Al-Imaroh based on teacher perception. This study uses a quantitative approach with a correlational analytical design. The population in this study is all teachers at MTs Al-Imaroh with sampling techniques using total sampling. Data collection was carried out through a Likert scale questionnaire that has been tested for validity and reliability. Data analysis used descriptive and inferential statistics, namely Pearson correlation tests and simple linear regression. The results of the study show that the role of school principals as innovators is in the good category, as well as the development of digital learning.